Legitimate Targets: What is the Applicable Legal Framework Governing the Use of Force in Rio de Janeiro?. Issue 1 (16th November 2022) - Foley, Conor
The belief that the favelas of Rio de Janeiro constitute a 'war zone' is widely held in Brazilian society. The intensity of the violence and the level of organization of some of the armed actors are comparable to those in officially recognized non-international armed conflicts elsewhere in the world. As conflicts are increasingly fought in situations where it is challenging to distinguish civilians from combatants, the binary divisions of international law are failing to address the contemporary experience of violence in what has been termed the 'new wars'. There is an emerging agreement in international jurisprudence and state practice that the provisions of international human rights law and international humanitarian law must be concurrently applied in officially recognised 'war zones'. This article argues that this analysis could also be used in other situations of violence, such as Rio de Janeiro, but the 'armed conflict' rhetoric risks conferring legitimacy of the use of lethal force between its parties.